(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the author examines the role of the Huaqiao on Malaysian society. The Chinese Huaqiao diaspora is the largest in the world. Its representatives live in 154 countries around the world.